Phantasmagoric Accounting: Research and Analysis of Economic, Social and Environmental Impact of Corporate Business, Studies in Accounting Research No. 14. - Boynton, William C. (The Accounting Review, 1978)
Abstract Reviews the book "Phantasmagoric Accounting: Research and Analysis of Economic, Social and Environmental Impact of Corporate Business: Studies in Accounting Research No. 14," by Robert E. Jensen.